Training Collaboration in the Field of National Defense and Security Education at Vietnam National University, Hanoi - Ngoc Sang, Tran; Ha, Nguyen Manh (VNU Journal of Science: Education Research; Vol 39 No 1SDO - 10.25073/2588-1159/vnuer.4848, 2023)
Before the new demands and tasks of safeguarding the Fatherland in the new situation, the education and cultivation of national defense and security knowledge is the right and responsibility of every citizen. Accordingly, students from colleges, universities nationwide in general, and the Hanoi region in particular, need to be educated to enhance their awareness of the Party's direction and the work of national defense and security, as well as the necessary and appropriate military knowledge and skills, to be ready to participate in fulfilling military duties when necessary. VNU National Defense and SecurityTraining Center, with its assigned functions and tasks, carries out the regular and important mission of organizing the linkage of national defense and security education with affiliated units according to the categorization of the Ministry of National Defense. Since its establishment until now, VNU National Defense and SecurityTraining Center has consistently organized the effective coordination of training in the field of national defense and security education for students from educational institutions in various categories, with tens of thousands of courses to meet training objectives and requirements, successfully completing the mission. Alongside the achieved results, the implementation process has encountered limitations and shortcomings that have had a certain impact on overall activities. This places a demand on VNU National Defense and SecurityTraining Center to continue researching content and methods for better implementation of training linkage with affiliated units, contributing to the enhancement of training quality.